Uganda : Report on the Prices Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report discusses the technical advice and recommendations given by the IMF mission to the authorities of Uganda about the concepts and methods used to compile the consumer price index (CPI). The conceptual basis of the rebased CPI was extensively discussed during the IMF mission. The rebasing was considered to be an opportunity to change the conceptual basis of the CPI and to compile weights using the domestic concept. The Uganda National Household Survey (UNHS) data were compared with household consumption derived in the supply and use tables. Tobacco and beer for instance are significantly underreported in the UNHS. Adjustment of the weight for under- or overreporting by comparing the UNHS data to other sources is recommended.